1991
DOI: 10.1104/pp.96.4.1214
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Tissue Print Analyses of Hydroxyproline-Rich Glycoproteins in Cell Walls of Sporophytic Maize Tissues

Abstract: In an effort to understand the role of hydroxyproline-rich glycoproteins (HRGPs) in plant cell wall structure, we studied the distribution and physical properties of PC-1-like proteins (PC-1 being the major pericarp HRGP) throughout sporophytic tissues of two maize (Zea mays L.) varieties. We determined total amounts of hydroxyproline, an indicator of HRGPs, and did tissue print and Western blot analysis. We found hydroxyproline in cell walls of stems, leaves, roots, tassels, and silks. We also observed reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The observation of cell wall proteins by this technique was demonstrated at first by Cassab and Varner (1987). It is reported to be a quick and easy method for detecting proteins/HRGPs in different plant tissues (Keller et al 1988;Fritz et al 1991;Hood et al 1991). The results obtained showed accumulation of HRGPs in a tissue-specific manner, being highest in the cell walls of epidermal cells and vascular bundles.…”
Section: Discussionmentioning
confidence: 97%
“…The observation of cell wall proteins by this technique was demonstrated at first by Cassab and Varner (1987). It is reported to be a quick and easy method for detecting proteins/HRGPs in different plant tissues (Keller et al 1988;Fritz et al 1991;Hood et al 1991). The results obtained showed accumulation of HRGPs in a tissue-specific manner, being highest in the cell walls of epidermal cells and vascular bundles.…”
Section: Discussionmentioning
confidence: 97%
“…By tissue printing, maize HRGP was localized in the vascular bundle and the epidermis of stem, leaves and tassel stalks. Silk prints stained strongly and did not seem to show any cell-type specificity (Hood et al, 1991a). …”
Section: Cellular Localization Of Hrgp Nirna and Polypeptidesmentioning
confidence: 99%
“…It has long been known that styles secrete AGPs Clarke et al, 1979). More recently, a PRP has been localized to the transmitting tract of tobacco styles (Wang et al, 1993), an HRGP with characteristics of both AGPs and extensins has been extracted from the transmitting tissue fluid of Nicotiana alata (Lind et al, 1994), and antibodies to a maize extensin-like protein have been shown to cross-react with proteins in maize silks (Hood et al, 1991). In addition, a number To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%